Application of graphene oxide membranes for removal of natural organic matter from water. (April 2018) - You, Y.; Jin, X.H.; Wen, X.Y.; Sahajwalla, V.; Chen, V.; Bustamante, H.; Joshi, R.K.
Abstract: Changes in the complexity of natural organic matter (NOM) have impacted the performance of direct filtration plants of water industries, resulting in reduced treatment capacity, and can lead to increased disinfection by-products. Hence, the need to identify new materials in future can be converted into more effective technologies and processes. We report a laboratory scale innovative use of graphene oxide membranes to remove NOMs from water that had been treated and still contained 5 mg/L DOC. Our study shows that graphene oxide based membranes can reject ∼100% of NOM while maintaining high water flux of 65 L m −2  h −1 bar −1 at atmospheric pressure. Our results indicate that it is possible to develop a graphene oxide-based water filtration technology. Graphical abstract: Image